1995
DOI: 10.1007/bf01215640
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a projection from the perireticular thalamic nucleus to the dorsal thalamus in the adult rat and ferret

Abstract: During early development, the perireticular thalamic nucleus is very large (i.e. has many cells) and has a strong projection to the dorsal thalamus and to the cerebral neocortex. By adulthood, the nucleus has much reduced in size and only a few cells remain. It is not clear whether these perireticular cells that remain into adulthood maintain their connections with the dorsal thalamus and with the neocortex. This study examines this issue by injecting neuronal tracers into various nuclei of the dorsal thalamus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…An auditory sector in the cat's PRN is defined here by the location of its cells that project to the MGv, MGdr, MGd, or MGm. Like in the rat (Mitrofanis et al, 1995), this sector is confined to a small caudoventral region of the PRN that lies opposite the auditory sector of the TRN. In the cat, the efferent connections of the PRN with the MGv and the MGdr are sparse, whereas those with the MGd and the MGm are robust.…”
Section: Auditory Sector Of the Prnmentioning
confidence: 94%
See 1 more Smart Citation
“…An auditory sector in the cat's PRN is defined here by the location of its cells that project to the MGv, MGdr, MGd, or MGm. Like in the rat (Mitrofanis et al, 1995), this sector is confined to a small caudoventral region of the PRN that lies opposite the auditory sector of the TRN. In the cat, the efferent connections of the PRN with the MGv and the MGdr are sparse, whereas those with the MGd and the MGm are robust.…”
Section: Auditory Sector Of the Prnmentioning
confidence: 94%
“…In the cat, the efferent connections of the PRN with the MGv and the MGdr are sparse, whereas those with the MGd and the MGm are robust. The PRN also contains sectors that are related to visual and somatosensory nuclei of the dorsal thalamus (Mitrofanis et al, 1995;Crabtree, 1996).…”
Section: Auditory Sector Of the Prnmentioning
confidence: 99%
“…Both PV and GABA were demonstrated in the PRT of adult cats and ferrets (Clemence and Mitrofanis, 1992), whereas we here provide evidence that in rats, PV-ir neurons do not contain GABA. As in rats, the neurons of the RT contain both PV and GABA throughout the postnatal development (De Biasi et al, 1986Celio, 1990;Frassoni et al, 1991), our results indicate that the PV-ir neurons of the PRT represent a distinct population from those of the RT, as suggested also from their different projections (Mitrofanis and Baker, 1993;Adams and Baker, 1995;Mitrofanis et al, 1995) and from our ultrastructural investigation (see below).…”
Section: Gaba Immunolocalizationmentioning
confidence: 64%
“…In particular, PRT neurons projecting to the cortex were localized mainly in the dorsal part of the IC (Adams and Baker, 1995), where we never found PV-ir neurons, and those projecting to the adult rat thalamus were detected only in the caudalmost (auditory) region of the IC (Mitrofanis et al, 1995), where we found only rare PV-ir neurons. Finally, Earle and Mitrofanis (1996) described, by means of quantitative methods on Nissl-stained sections, an almost complete loss of PRT cells by P15.…”
Section: Distribution Of Pv-ir Neuronsmentioning
confidence: 81%
See 1 more Smart Citation